Supplementation of IVM media with equine follicular fluid of large follicles increases blastocyst yield in equine ICSI programs - Luciana Ribeiro Peixoto; Marcos Antônio Gonçalves; José Henrique Fortes Pontes; Perla Dagher Cassoli Fleury; Gustavo Pulzatto Merlini; Thiago Alexandre Robilotta de Oliveira; Victoria Martins Braghetto Barillari; Cláudia Barbosa Fernandes; José Buratini; Vilceu Bordignon; Felipe Perecin (Theriogenology, 2026)

Renal proteomics of male offspring exposed to maternal protein restriction: molecular, epigenetic, and nephron-specific signatures of metabolic programming - Danielle Amanda Niz Alvarez; Isabelle Tenori Ribeiro; Matheus Naia Fioretto; Marina Pereira Pires; Luisa Annibal Barata; Flávia Alessandra Maciel; Luiz Marcos Frediane Portela; Renato Mattos; Hecttor Sebastian Baptista; Pedro Menchini Vitali¹; Vinicius Alexandre Andrade Felipe; Marcel Rodrigues Ferreira; et al. (Journal of Physiology and Biochemistry, 2026)
Chronic kidney disease is an increasing global public health concern, and the Developmental Origins of Health and Disease (DOHaD) concept proposes that adverse conditions during critical developmental windows predispose offspring to chronic disorders later in life. Maternal protein restriction (MPR), a well-established experimental model reflecting food insecurity, has been shown to impair nephrogenesis and promote long-term renal dysfunction. In this study, we investigated renal metabolic–epigenetic programming induced by gestational and lactational MPR in post-weaning male rats using a global kidney proteomic approach. MPR altered renal structure and profoundly dysregulated protein networks, characterized by downregulation of energy metabolism, ion transport, cytoskeletal organization, membrane integrity, and mitochondrial function, alongside upregulation of innate immune pathways, glutathione metabolism, vesicular trafficking, and cytoskeletal dynamics. Integrated pathway and disease enrichment analyses revealed the potential risk to hypertension, acid–base imbalance, renal tubular transport disorders, nephrosis, and renal failure. Key differentially expressed proteins (e.g., GPX1, CYCS, ATP1A2/ATP1B1, TUBB/TUBA isoforms, ANPEP, and metabolic enzymes) emerged as potential biomarkers of renal metabolic–epigenetic programming. Collectively, these findings identify molecular signatures that link early-life protein restriction to long-term risk of kidney disease and provide mechanistic insight into the nephron- and cell-specific consequences of MPR.

Wildfire smoke, PM2.5 exposure and respiratory morbidity in a densely populated urban setting: Spatial mapping and time-series evidence - Egle Gabriele Castanha de Souza; Bruno Iartelli Silva; Alexandre Matos Muniz Matias; Luis Felipe de Almeida Duarte (Science of The Total Environment, 2026)

The Missing Branches of the Bee Tree of Life: Addressing Global Darwinian Shortfalls and Their Drivers - Felipe Walter Pereira; Matheus Lima Araujo; Anderson Lepeco; Bruno Ferreira Marques; Hugo Bampi; Lucas Jardim; Luísa Vareira; Luisa G. Carvalheiro; Thiago F. Rangel; José Alexandre F. Diniz Filho (Journal of Biogeography, 2026)
Aim Estimate the Darwinian shortfall (i.e., the lack of knowledge about phylogenetic relationships) of bees worldwide, as well as identify their drivers. Location Global. Taxon Bees (Hymenoptera, Anthophila). Methods We built phylogenies for over 12,000 bee species, combining the most comprehensive phylogeny and an algorithm with random solutions to insert missing lineages. The Darwinian shortfall was quantified as the Phylogenetic Diversity (PD) deficit, the ratio of inserted branch lengths at the assemblage level. We identified potential ecological and socioeconomic drivers of the Darwinian shortfall using Simultaneous Autoregressive (SAR) models. Results The highest shortfalls were identified in the Southern Hemisphere. Mean species range size and species richness were the strongest drivers, as smaller ranges and higher richness were associated with higher deficits. Per capita GDP was negatively associated with PD deficits, while population and road densities showed positive but weak effects. Sample completeness had a weaker effect, limited by missing occurrence data in many regions. Main Conclusions Our findings underscore the need for integrative efforts combining taxonomy, data digitization, adequate research investments, and targeted sampling, especially in the Global South. Overcoming the Darwinian shortfall is essential to develop robust strategies to preserve the Tree of Life, especially for one of the most important groups of pollinators while facing the ongoing biodiversity crisis.

Cytogenotoxic effects of Artocarpus heterophyllus Lam. leaf extracts: implications for the safe use of medicinal plants - Ellen Borges da Rocha; Renata Gomes Gonçalves; Brenda Christie Castro de Oliveira; Alexia Barreto da Silveira; Ana Beatriz Franco de Jesus; Luiz Carnevale Eberhardt; Débora Moura Peixoto; Brena Guerra Paixão; Matheus de Lima Rodrigues; Alexandre Felipe de Araújo Desidério; Dayana Palmeira da Silva Rosa; Helena Regina Pinto Lima; et al. (South African Journal of Botany, 2026)

Cover crops shape soil microbiome and ecological interactions in the soybean rhizosphere under long-term no-till - Caio César Gomes Freitas; Carolinne Rosa de Carvalho; Nariane de Andrade; Rafael Lima Oliveira; Victor Lucas Vieira Prudêncio Araújo; Felipe Martins do Rêgo Barros; João Henrique dos Santos Ferreira; José Roberto Portugal; Carlos Alexandre Costa Crusciol; Fernando Dini Andreote (Soil and Tillage Research, 2026)

The alginate-carrageenan blend exhibits good printability and supports adhesion of ovarian stromal cells in bioprinted scaffolds - Solano Dantas Martins; Iana Lira Nogueira; Maria Alice Felipe Oliveira; Pedro Everson Alexandre De Aquino; Marjory Lima Holanda Araújo; Vânia Marilande Ceccatto; Valdevane Rocha Araújo (Reproductive Biology, 2026)

Plant Growth-Promoting Microorganisms (PGPMs) in Plant Tissue Culture: Roles in Regeneration, Metabolism, and Acclimatization - Sérgio Heitor Sousa Felipe; Anyela Marcela Ríos-Ríos; Irislene Cutrim Albuquerque; Jordanya Ferreira Pinheiro; Vitória Karla de Oliveira Silva-Moraes; Juliane Maciel Henschel; Tatiane Dulcineia Silva; Evandro Alexandre Fortini; Vanessa Nascimento Brito; Thais Roseli Corrêa; Diego Silva Batista; Wagner Campos Otoni (Journal of Plant Growth Regulation, 2026)
Plant tissue culture offers a controlled platform for biodiversity conservation, clonal propagation, and the production of bioactive compounds; however, the exclusion of natural microbial partners limits morphogenesis, aerial and root system development, and acclimatization success. Biotization with Plant Growth-Promoting Microorganisms (PGPMs) has emerged as a strategy to re-establish functional plant-microbe interactions disrupted by axenization. This review compiles advances on PGPMs in plant tissue culture, emphasizing their roles in regeneration, secondary metabolism, and acclimatization, while identifying prospects for applied biotechnology. PGPMs influence phytohormone profiles, nutrient acquisition, and defense pathways, thereby improving rhizogenesis, shoot morphogenesis, and acclimatization performance. Molecular evidence indicates that PGPMs modulate hormonal signaling and nutrient assimilation pathways, providing a mechanistic basis for these beneficial effects. Studies demonstrate that endophytic bacteria, rhizobacteria, actinomycetes, and mycorrhizal fungi can enhance regeneration efficiency and promote stress tolerance in vitro. Despite these advances, the specificity of microbial strains, colonization dynamics, and long-term stability of plant-microbe associations remain poorly resolved. Standardized inoculation protocols combined with integrative multi-omics approaches will enable the rational design of host-specific microbial consortia and accelerate the translation of PGPM-based biotization into reproducible and scalable micropropagation systems.

Retraction notice to “Spatial and temporal distribution of urban heat islands” [Sci. Total Environ. 605–606 (2017) 946–956] - Alexandre Rosa dos Santos; Felício Santos de Oliveira; Aderbal Gomes da Silva; José Marinaldo Gleriani; Wantuelfer Gonçalves; Giselle Lemos Moreira; Felipe Gimenes Silva; Elvis Ricardo Figueira Branco; Marks Melo Moura; Rosane Gomes da Silva; Ronie Silva Juvanhol; Kaíse Barbosa de Souza; et al. (Science of The Total Environment, 2026)

Embryo-fetal and early-life protein restriction programs pulmonary structure and molecular parameters in both dams and female offspring - Flávia Alessandra Maciel; Matheus Naia Fioretto; Luisa Annibal Barata; Isabelle Tenori Ribeiro; Vinícius Alexandre de Andrade Felipe; Lucas Sobrinho Lemos; Maycon Tavares Emílio-Silva; Tainá Dorte da Silva; Flávia Karina Delella; Clélia Akiko Hiruma Lima; Wellerson Rodrigo Scarano; Luis Antonio Justulin (Molecular and Cellular Biochemistry, 2026)
The Developmental Origins of Health and Disease (DOHaD) theory proposes that adverse conditions during critical developmental windows can increase disease susceptibility throughout life. Maternal protein restriction (MPR) is a well-established experimental model that impairs offspring lung development, affecting pulmonary structure, metabolism, and molecular pathways from early life to aging. However, little is known about its effects on maternal pulmonary health and female offspring, representing an important gap in the literature. Therefore, this study investigated the effects of MPR on lung structure and metabolism in dams at the end of lactation and in female offspring at weaning. Sprague Dawley rats were fed either a control diet (17% protein) or a low-protein diet (6% protein) throughout gestation and lactation. Dams and female offspring were euthanized at weaning, and pulmonary alterations were assessed through histological, biochemical, molecular, zymographic, and in silico analyses. MPR increased collagen deposition, mast cell density, and Acta expression, while reducing reticular fibers in maternal lungs, accompanied by a trend toward increased lipid peroxidation. In female offspring, MPR reduced alveolar diameter, mast cell density, and reticular fibers, while increasing collagen deposition, MMP-2 activity, PI3K and MyoD expression, and decreasing mTOR expression as well as Nduf transcript levels. No significant alterations in antioxidant parameters were observed in either dams or offspring. Integrative analyses indicate that MPR promotes structural remodeling in maternal lungs, potentially compromising ventilatory function. In female offspring, MPR induces delayed pulmonary development, extracellular matrix remodeling, alterations in smooth muscle-related pathways, and disturbances in energy metabolism. Together, these findings demonstrate that maternal protein resQ1triction adversely affects pulmonary health in both dams and female offspring, revealing potential mechanisms linking early-life nutritional adversity to the developmental origins of respiratory disease.

Maternal parity modulates the impact of lactation management on fetal programming of postnatal performance in Nelore bulls - Alessandra Regina Carrer; Rubens Paes de Arruda; Guilherme Pugliesi; Felipe Zandonadi Brandão; Isabella Rio Feltrin; Júlio César de Carvalho Balieiro; Paulo Roberto Leme; Arlindo Saran Netto; Rodrigo Silva Goulart; Germán Darío Ramirez Zamudio; Karine Galhego Morelli; Alexandre Rossetto Garcia; et al. (Theriogenology, 2026)

Legacy P from rock phosphate promotes growth of eucalypt coppice stands without further P application - Adam da Cruz Rodrigues; Cassio Rafael Costa dos Santos; Maria Leidiane Reis Barreto; Felipe Tavares Lima; Antonio Leite Florentino; Alexandre de Vicente Ferraz; José Leonardo de Moraes Gonçalves (Forest Ecology and Management, 2026)

Corrigendum to “Response of phytoplankton to eddy dipole structure in the Mozambique channel: An automated underway evaluation” [Deep-Sea Res. 224 (2025) 105554] - Jordan Toullec; Millat Blanc; Pierrick Penven; Alexandre Epinoux; Natasha Buckiewicz; Emmanuelle Jaouen; Valentine Szrama; Margaux Noyon; Jean-François Ternon; Luis Felipe Artigas (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Optimizing soybean breeding: High-throughput phenotyping for stink bug resistance and high yields - Maiara de Oliveira; Alexandre Hild Aono; Patricia Braga; Adriano Abreu Moreira; Fernanda Smaniotto Campion; Felipe Augusto Krause; Fernando Henrique Iost Filho; Juliano de Bastos Pazini; Pedro Takao Yamamoto; José Baldin Pinheiro (Precision Agriculture, 2026)
Background: The stink bug complex is one of the most damaging pests of soybean, reducing yield and seed quality. Genetic resistance remains the most sustainable and effective management strategy, but its quantitative inheritance and labor-intensive field phenotyping make its implementation in breeding programs challenging. Objective: This study explored high-throughput phenotyping (HTP) using unmanned aerial vehicles (UAVs) equipped with RGB cameras to evaluate a soybean population and the potential of phenotyping to stink bug resistance by correlating image-derived features and machine learning (ML) models. Methods: A population of 304 soybean lines was evaluated in alpha-lattice design trials across two seasons under natural infestations. Five resistance-related traits, grain yield (GY), healthy seed weight (HSW), number of days to maturity (NDM), tolerance (TOL), and leaf retention (LR), were manually scored and linked to UAV-derived vegetation indices (VIs) and texture indices (TIs). Three ML models (AdaBoost, SVM, MLP) were tested to predict these traits from aerial features. Results: Results showed that VIs, particularly Visible Atmospherically Resistant Index at the 25th percentile (VARI_P25), were consistently associated with resistance-related traits, while decision tree analysis highlighted TIs at 45° and 135° as complementary sources of structural information. Prediction ability was highest for GY, HSW, and NDM, especially in flights near flowering and maturity, but remained low for TOL and LR. Integrating multiple flights modestly improved accuracy, whereas cross-season predictions were unreliable. Nonetheless, indices such as VARI_P25 provided useful cross-season correlations for HSW and TOL, enabling early screening of less promising lines. Conclusion: This pioneering study demonstrates that UAV–ML pipelines can capture genetic signals of stink bug resistance in soybean, despite environmental complexity. These findings open new avenues for resistance phenotyping, supporting more efficient breeding strategies and accelerating genetic gains in soybean improvement.

Modeling longitudinal changes of maximal short-term power outputs in young volleyball players: a Bayesian analysis - Humberto M. Carvalho; André L. A. Soares; Alexandre M. Oliveira; Luciano G. Galvão; Fábio C. Karasiak; Felipe G. Mendes; Rui Resende; Carlos E. Gonçalves (German Journal of Exercise and Sport Research, 2026)

Optimization of corneal preservation media with novel antifungal agents - Paula Reginatto; Giovanna de Jesus Agostinetto; Claudete Inês Locatelli; Felipe Silva Guareze; Angélica Rocha Joaquim; Maria Eduarda Krummenauer; Rúbia do Nascimento Fuentefria; Marilene Henning Vainstein; Diane Ruschel Marinho; Saulo Fernandes de Andrade; Alexandre Meneghello Fuentefria (Archives of Microbiology, 2026)
The performance of ophthalmic surgeries, particularly penetrating keratoplasty, is associated with an increased risk of ocular infections, especially fungal keratitis. In addition to infections such as post-surgical occlusions, microbial contamination of the donor’s tissue, predominantly fungal in nature, can also lead to the disposal of said tissue. The genus Fusarium , along with several species from the Candida genus, emerge as the primary fungal agents, displaying notable biofilm-forming abilities on surfaces. To address these issues, the addition of antifungals to preservation media vials has been explored, although conventional antifungal agents exhibit limitations. In light of this, compounds such derived from 8-hydroxyquinoline, clioquinol (CLQ) and PH151, emerge as promising alternatives. Hence, this study aimed to assess the efficacy of two derivatives of 8-hydroxyquinoline, both individually and in combination with antifungal agents, as additives in preservation media for human corneas intended for transplantation. Given the antifungal potential of CLQ and the combination voriconazole-amphotericin B-clioquinol, the ability to inhibit fungal growth and biofilm formation in human corneas preserved in Optisol-GS medium was investigated, as well as the endothelial viability of this tissue in the presence of these compounds. Among the tested antifungal agents, the combination of voriconazole, amphotericin B, and clioquinol stood out for its excellent antibiofilm action and potential to reduce the fungal load on the surface of the corneas, did not present endothelial toxicity. Thus, the results underscore the promising nature of this combination as a potential additive in hypothermic corneal preservation media, outlining a viable pathway to enhance corneal transplant efficacy.

Physiological and Proteomic Shifts in Pfaffia glomerata Under Drought and Elevated CO₂ - Tatiane Dulcineia Silva; Evandro Alexandre Fortini; Diego Silva Batista; Kerly Jessenia Moncaleano Robledo; Mariana Machado; Sérgio Heitor Sousa Felipe; Tadeu dos Reis de Oliveira; Moab Torres de Andrade; Letícia Monteiro Farias; Claudete Santa-Catarina; Vanildo Silveira; Philipp Westhoff; et al. (Journal of Plant Growth Regulation, 2026)
Drought is a major constraint to plant growth and productivity, and rising atmospheric CO₂ concentrations are expected to modify plant responses to water limitation. However, how CO₂ enrichment reshapes the physiological, metabolic, and molecular regulation of specialized metabolite production under drought remains poorly understood. Here, we investigated the combined effects of elevated CO₂ (e[CO₂]) and drought on plant morphophysiology and on the production of 20-hydroxyecdysone (20E), a phytoecdysteroid of therapeutic relevance whose accumulation may be influenced by environmental stress, in Pfaffia glomerata . Plants were grown under ambient (± 400 µmol mol⁻ 1 ; a[CO₂]) or elevated (± 800 µmol mol⁻ 1 ; e[CO₂]) CO₂ concentrations combined with sufficient or limited water supply. Elevated CO₂ promoted a metabolic shift under drought, characterized by increased investment in osmoregulatory compounds, including soluble sugars, myo-inositol, and glutamate. In contrast, drought reduced photosynthetic pigments and several primary metabolites regardless of CO₂ level. Drought induced the expression of lignin biosynthesis genes ( PgC4H , PgCCoAOMT , and PgCAD ) under both CO₂ conditions; however, PgCCR was specifically upregulated under e[CO₂] combined with drought, with consistently higher transcript levels than under ambient CO₂. Proteomic analyses revealed that e[CO₂] attenuated the accumulation of many canonical drought-responsive proteins, while selectively promoting the accumulation of the cytochrome P450 CYP72A219-like protein, which was associated with increased whole-plant 20E production. Together, these findings show that drought drives 20E biosynthesis, while elevated CO₂ modulates drought response intensity and allocation, ultimately affecting total 20E yield per plant and its relevance under future climate scenarios.

Correction: Small muscle mass exercise enhances muscular adaptations? Effects of unilateral and bilateral biceps curl on maximum strength and muscle size changes - Witalo Kassiano; Ian Tricoli; Felipe Gomes; Vanessa Santos-Melo; Ingrid Manske; Gabriel Kunevaliki; Felipe Lisboa; Alexandre Miguel; Aline Prado; Natã Stavinski; Edilson S. Cyrino (European Journal of Applied Physiology, 2026)

Small muscle mass exercise enhances muscular adaptations? Effects of unilateral and bilateral biceps curl on maximum strength and muscle size changes - Witalo Kassiano; Ian Tricoli; Felipe Gomes; Vanessa Santos-Melo; Ingrid Manske; Gabriel Kunevaliki; Felipe Lisboa; Alexandre Miguel; Aline Prado; Natã Stavinski; Edilson S. Cyrino (European Journal of Applied Physiology, 2026)

Differential expression of sperm capacitation-associated microRNAs in fresh and cryopreserved bovine semen - Laura Nataly Garcia-Oliveros; Alexandre da Rocha Bozzi; Thais de Oliveira Cardoso Silva; Fernanda Baatsch Nascimento; Thainara Rodrigues Oliveira; Maíra Bianchi Rodrigues Alves; Cibele Maria Prado Zinni; Yulizabeth Daniela Pinto Rojas; Juliano Coelho da Silveira; Felipe Perecin; Eneiva Carla Carvalho Celeghini (Animal Reproduction Science, 2026)

Tree planting in public squares in an Amazonian capital: are morphometric and ecological aspects considered for decision-making? - Hiago Felipe Cardoso Pacheco; Walmer Bruno da Rocha Martins; Julia Isabella de Matos Rodrigues; Joathan Cipriano Castro; Paula Daniele Martins Moraes; José Rozendo de Lima Silva; Marcos Alexandre Vieira Nascimento Filho; Lucas Lopes da Silva (Trees, 2026)
Key message This study highlights native species’ potential for urban landscaping in the Amazon region, prioritizing safety and ecosystem benefits. Abstract Public squares can be important elements for sustainable urban development and adaptation to climate change, for which an adequate tree composition is key. In the Amazon region, despite the high tree biodiversity, it is common to select unfitted species to compose public squares’ landscaping. Therefore, this research aimed to evaluate the suitability of species used for landscaping of public squares in an Amazonian state capital, based on 4 morphometric and 3 ecological features. 50 public squares were selected and inventoried, tree species were evaluated and classified according to morphometric features (crown projection, slenderness, overhang index, and coverage index), as well as ecological features (leaf habit, fruit weight, and species origin). Species were ranked from the most to the least suitable using weighted values based upon the 7 features employed. The results indicated that, within species currently in used in Belém public squares, Andira inermis (W.Wright) DC. (Cabbage bark) and Ceiba pentandra (L.) Gaertn. (Kapok tree), native to the Amazon region, were the most fitted for public squares landscaping among all the species encountered. Native species such as Bertholletia excelsa Bonpl. (Brazil nut) and Swietenia macrophylla King (Brazilian mahogany), although promising, showed limitations due to their high weighted fruits. This study highlights the need for further research on the use of native Amazonian flora in public squares, especially on its regulating and cultural ecosystem services provision in urban contexts. Additionally, it emphasizes that the implementation of some species should be discontinued due to risks to the safety of urban square visitors and possible damage to urban infrastructure.

Acute toxicity and redox-modulating potential of nanoparticles loaded with phenolic compounds from cantaloupe melon (Cucumis melo L.) in zebrafish (Danio rerio) - Aslan Costa Trajano; Ana Carolina Luchiari; Yasmim Pessoa de Oliveira; Jéssica Anarellis Barbosa dos Santos; Beatriz Silva Lopes; Cristiane Fernandes de Assis; Hugo Alexandre Oliveira Rocha; Weslley de Souza Paiva; Susana Margarida Gomes Moreira; Pablo Felipe Ferreira Farias; Ana Heloneida de Araújo Morais; Thaís Souza Passos (Food Research International, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Silvopastoral system versus unwooded pastures: changing the mindset to combine animal welfare and profitable performance in cattle farming - Mariana Jucá Moraes; Júlio Cesar de Carvalho Balieiro; Felipe Tonato; André de Faria Pedroso; José Ricardo Macedo Pezzopane; Felipe Zandonadi Brandão; Erick Fonseca de Castilho; Andréa do Nascimento Barreto; Lívia Ferreira Pinho; Giovanna Galhardo Ramos; Alexandre Rossetto Garcia (Agroforestry Systems, 2026)
Tropical zones currently produce the majority of the world’s agricultural food; however, their thermal environment poses a challenge to animals. In this context, silvopastoral systems (SPS) have been proposed to provide animals with milder microclimates owing to their shaded areas. To evaluate the impact of the silvopastoral system on the behavior, gonadosomatic development, and endocrine profile of young beef bulls, as well as to relate these characteristics to thermal comfort conditions across different seasons. Conducted over 13 months in a high-altitude tropical area in Brazil, the study involved 40 beef bulls (10.5±1.9 months; 222.5±34.5 kg BW), divided into full sun (FS; n=20) and SPS (n=20). Weather stations measured bioclimatic variables, and electronic collars permanently monitored animal behavior. Monthly measurements included hormonal profiles, live weight, and scrotal circumference. Statistical analyses used a mixed linear model (α=5%).SPS provided a milder microclimate, enhancing thermal comfort ( P P P P

Breed-specific testicular ultrasound profiles and pubertal markers in Bos indicus and composite bulls - Joedson Dantas Gonçalves; Maria Emilia Franco Oliveira; Rubens Paes de Arruda; Cintia Righetti Marcondes; Patrícia Tholon; Felipe Zandonadi Brandão; Gabriela Novais Azevedo; Giovanna Galhardo Ramos; Gabriel Brun Vergani; Alexandre Rossetto Garcia (Theriogenology, 2026)

Predictive empirical modeling of halogenated by-products during raw water pre-chlorination stage: Toward optimized chlorine dosing - Cristina Filomêna Pereira Rosa Paschoalato; Aline Branco de Miranda Lazari; Márcia Maísa de Freitas Afonso; Felipe Alexandre Gonçalves; Guilherme Sgobbi Zagui; Marília Vasconcellos Agnesini; Murilo Daniel de Mello Innocentini; Danilo Vitorino dos Santos; Susana Inés Segura-Muñoz (Journal of Water Process Engineering, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Kinetics of thermochemical sulfate reduction based on pyrolysis gold-tube experiments on lacustrine oil: Implications for H2S prediction in Brazilian pre-salt reservoirs - Igor V.A.F. Souza; Yongchun Tang; Le Lu; Alexandre A. Ferreira; Geoffrey S. Ellis; Rut A. Díaz; Luiz Felipe Carvalho Coutinho; Ana Luiza S. Albuquerque (Marine and Petroleum Geology, 2025)

The tastiest is not always the safest: mercury risks of boneless fish consumption compared to other seafood traded in southeastern Brazil - Alice de Souza Picaluga; Monizze Vannuci-Silva; Lucas Rodrigues Tovar; Petrus Magnus Amaral Galvão; Hugo Felipe Gonçalves da Silva; Haydée Andrade Cunha; Alexandre F. Azevedo; Olaf Malm; José Lailson-Brito; Tatiana Lemos Bisi (Food and Chemical Toxicology, 2025)

Catastrophic wildfires in the Pantanal wetlands as catalysts for transformative change - Alexandre de Matos Martins Pereira; Geraldo Alves Damasceno-Junior; Renata Libonati; Liana O. Anderson; Allan Henrique de Almeida Souza; Bruno Henrique dos Santos Ferreira; Andre Valle Nunes; André Luiz Siqueira; Angelica Guerra; Angelo Cipriano Pacelli Rabelo; Arnaud L.J. Desbiez; Arthur Henrique Leite Falcette; et al. (Environmental Science & Policy, 2025)

Response of phytoplankton to eddy dipole structure in the Mozambique channel: An automated underway evaluation - Jordan Toullec; Millat Blanc; Pierrick Penven; Alexandre Epinoux; Natasha Buckiewicz; Emmanuelle Jaouen; Valentine Szrama; Margaux Noyon; Jean-François Ternon; Luis Felipe Artigas (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Traditional ecological knowledge of scorpions in human communities in a Brazilian semiarid region - Luiza Eulália de Azevedo Gonzaga; José Rivaldo de Lima; Meykson Alexandre da Silva; Geraldo Jorge Barbosa de Moura; André Felipe de Araujo Lira (International Journal of Tropical Insect Science, 2025)

Antibacterial and antibiofilm activity of ruthenium polypyridine complex against Staphylococcus strains - Leonardo Silva de Sousa; Alexandre Lopes Andrade; Aryane de Azevedo Pinheiro; Felipe Diógenes Abreu; Eduardo Henrique Silva Sousa; Idalina Maria Moreira de Carvalho; Débora S. C. M. Castelo-Branco; Mayron Alves de Vasconcelos; Edson Holanda Teixeira (Biofouling, 2025)

Litter removal has long-lasting harmful effects on nutrient dynamics in a tropical secondary forest - Julia Isabella de Matos Rodrigues; Walmer Bruno Rocha Martins; Victor Pereira de Oliveira; Luiz Fernandes Silva Dionísio; Hiago Felipe Cardoso Pacheco; Marcos Alexandre Vieira Nascimento Filho; Manoel Tavares de Paula; Francisco de Assis Oliveira; Gustavo Schwartz (Plant and Soil, 2025)

Plant-soil microbiome feedback under post-pasture tropical ecotone forest regeneration - Franciele Muchalak; Anderson Santos de Freitas; Luís Felipe Guandalin Zagatto; Gabriel Silvestre Rocha; Guilherme Lucio Martins; Solange dos Santos Silva-Zagatto; Thierry Alexandre Pellegrinetti; Siu Mui Tsai; Acacio Aparecido Navarrete (Applied Soil Ecology, 2025)

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Intelligent optical fiber probe for rapid beer quality assessment - Felipe Oliveira Barino; João Victor Calderano; Renato Luiz Faraco-Filho; Alexandre Bessa dos Santos (Journal of Food Engineering, 2025)

Multiscale phytoplankton dynamics in a coastal system of the eastern English Channel: the Boulogne-sur-Mer coastal area - Kévin Robache; Zéline Hubert; Clémentine Gallot; Alexandre Epinoux; Arnaud P. Louchart; Jean-Valéry Facq; Alain Lefebvre; Michel Répécaud; Vincent Cornille; Florine Verhaeghe; Yann Audinet; Laurent Brutier; et al. (Ocean Science, 2025)
To study changes in phytoplankton community composition on different timescales, an automated flow cytometer (CytoSub, CytoBuoy b.v.) was deployed at the MAREL Carnot automated monitoring station in Boulogne-sur-Mer (eastern English Channel, France) during spring (2021 and 2022) and summer (2022), following an Eulerian approach. Phytoplankton dynamics were recorded every 2 h, distinguishing 11 phytoplankton functional groups (PFGs) based on optical and fluorescence properties. This enabled detailed characterization of PFG successions, including MicroRED (mostly diatoms) and NanoRED (mostly haptophytes of the species Phaeocystis globosa) transitions in spring, as well as a summer dominance by PicoORG (picocyanobacteria, mostly of the genus Synechococcus) and PicoRED. Four rare events, including a salinity drop (April 2021), strong winds (May 2021 and April 2022), and a marine heat wave (July 2022), caused rapid shifts in phytoplankton community assemblage. Empirical mode decomposition (EMD) and Lomb–Scargle periodogram (LSP) analyses revealed that 85±10 % of variability in total phytoplankton abundance, red fluorescence (a proxy of chlorophyll a), and Shannon diversity occurred on relatively short timescales (9 h to 11 d) for time series of several months, highlighting the value of high-frequency monitoring in capturing ecological dynamics under macrotidal conditions in the eastern English Channel.

Sulfated polysaccharides of Caulerpa cupressoides var. flabellata: An investigation into their antioxidant properties and biocompatibility - Pablo Felipe Ferreira Farias; Victor Moraes Rodrigues; Augusto Monteiro de Souza; Douglas Dourado Oliveira; Ana Carolina Luchiari; Hugo Alexandre Oliveira Rocha; Susana Margarida Gomes Moreira (Journal of Applied Phycology, 2025)

Bacterial and nematode communities associated with soybean-cultivated soils from two native Brazilian biomes - Felipe Martins do Rêgo Barros; Roy Neilson; Madeline Giles; Sandra Caul; Alexandre Pedrinho; Claudio Marcelo Gonçalves de Oliveira; Luiz Antônio da Silva; Victor Lucas Vieira Prudêncio de Araújo; Lucas William Mendes; Fernando Dini Andreote (Applied Soil Ecology, 2025)

Assessing sediment and nutrient transport in a South Brazilian catchment: hysteresis, fingerprinting, and management implications - Alice Prates Bisso Dambroz; Jean Paolo Gomes Minella; Paul David Capel; Felipe Bernardi; Larissa Werle; João Henrique Stibe Silva; Alexandre Augusto Schlesner; Lidiane Buligon; Fábio Joel Kochem Mallmann; Claudia Alessandra Peixoto de Barros; Tales Tiecher; Olivier Evrard; et al. (Environmental Monitoring and Assessment, 2025)

Two new species in the Tylopilus balloui -group (Boletaceae, Basidiomycota) from white-sand forests in Northeast Brazil - Juliane C. Valões-Araújo; Anderlechi Barbosa-Silva; Alexandre G.S Silva-Filho; Fernando Fabrini; Ricardo Koroiva; Felipe Wartchow (Plant Biosystems, 2025)

Fisheries bycatch threatens sessile communities of the Great Amazon Reef System - Afonso Luiz José Oliveira Silva; Alexandre Pires Marceniuk; George Joaquim Garcia Santos; Felipe Ferreira Campos; Anne Isabelley Gondim; Alex Garcia Cavalleiro de Macedo Klautau; Wagner Cesar Rosa Santos; Bruno Eleres Soares; Ronaldo Bastos Francini-Filho; Ralf Tarciso Silva Cordeiro (Estuarine, Coastal and Shelf Science, 2025)

Entropy-Based Measure of Rock Sample Heterogeneity Derived from Micro-CT Images - Luan Coelho Vieira da Silva; Júlio de Castro Vargas Fernandes; Felipe Bevilaqua Foldes Guimarães; Pedro Henrique Braga Lisboa; Carlos Eduardo Menezes dos Anjos; Thais Fernandes de Matos; Marcelo Ramalho Albuquerque; Rodrigo Surmas; Alexandre Gonçalves Evsukoff (Transport in Porous Media, 2025)

Genome-wide association reveals novel insights into the molecular mechanisms regulating stem volume in Pinus taeda - Alexandre Hild Aono; Stephanie Karenina Bajay; Felipe Roberto Francisco; Anete Pereira de Souza (Tree Genetics & Genomes, 2025)

Use of Vermicompost Modulates Physiological and Growth Responses of Paricá Seedlings more than Mineral Fertilization - Maria Leidiane Reis Barreto; Maria Bruna de Lima Oliveira; Milena de Cassia Silba Borges; Milton Garcia Costa; Renato de Mello Prado; Alexandre de Vicente Ferraz; Adam da Cruz Rodrigues; Felipe Tavares Lima; Jesus de Nazaré Santos Oliveira; Marta Oliveira da Silva; Eric Victor de Oliveira Ferreira; Cassio Rafael Costa dos Santos (Journal of Soil Science and Plant Nutrition, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Supplemental Feeding as a Driver of Population Expansion and Morphological Change in Anna's Hummingbirds - Nicolas M. Alexandre; Faye G. Romero; Simon G. English; Eliza Grames; Felipe Garzón‐Agudelo; Kevin Epperly; Timothy Barnes; Donald R. Powers; Audrey E. Smith; Zoë Migicovsky; Laura Stein; Saron Akalu; et al. (Global Change Biology, 2025)
Bird beaks are highly adaptable, with the potential to undergo rapid morphological shifts in response to environmental change such as climatic variation or food availability. Anna's Hummingbirds ( Calypte anna ) have undergone dramatic population range expansions over the last 160 years into novel climatic regimes, where supplemental feeders and introduced plant species are frequented. We used museum specimens to measure and characterize the shape of Anna's Hummingbird bills, hypothesizing that the introduction of novel food sources and the colonization of colder climates were associated with distinct dimensions of beak morphology. We estimated feeder and Eucalyptus availability using data from archived newspaper databases and found that these two abundances are linked to population increases in Anna's Hummingbirds, while feeders were associated with changes to beak morphology. We found that bill size and shape changed with feeder use, exhibiting a more tapered and longer bill and a distinct maxillary constriction. In males, dorsal bill shape increased in pointedness, which may have provided an advantage with increased agonistic encounters at feeders. In contrast, bill size decreased in association with lower temperatures at higher latitudes. Our data document rapid morphological changes in the Anna's Hummingbird's bill induced by human‐caused environmental changes over the last century.

Assessing genetics, biophysical, and management factors related to soybean seed protein variation in Brazil - María Sol Zelaya Arce; Eduardo Lago Lago Tagliapietra; José Eduardo Minussi Winck; Alexandre Ferigolo Alves; Felipe Schmidt Dalla Porta; Tiago Broilo Facco; Nereu Augusto Streck; Mauricio Fornalski Soares; Gregori Da Encarnação Ferrão; Daniel Debona; Claudio Hideo Martins da Costa; Rodrigo Merighi Bega; et al. (European Journal of Agronomy, 2025)

(Bio)Hybrid System of Layered Double Hydroxides and Dapsone: One-Pot Synthesis, Structural Characterization and Cell Viability - Felipe de Albuquerque Marinho; Amanda Damasceno Leão; Antônia Carla de Jesus Oliveira; Luise Lopes Chaves; Jessica Cavalcante Martins; Izabel Maria de Melo Amaral; Mylena Karolina Oliveira Do Amaral; Lucas José de Alencar Danda; Raiza Raianne Luz Rodrigues; Rafael Alexandre Raimundo; Klinger Antonio da Franca Rodrigues; Mônica Felts de La Rocca Soares; et al. (Journal of Pharmaceutical Innovation, 2025)

Decadal changes in phytoplankton functional composition in the Eastern English Channel: possible upcoming major effects of climate change - Zéline Hubert; Arnaud P. Louchart; Kévin Robache; Alexandre Epinoux; Clémentine Gallot; Vincent Cornille; Muriel Crouvoisier; Sébastien Monchy; Luis Felipe Artigas (Ocean Science, 2025)
Global change is known to exert a considerable impact on marine and coastal ecosystems, affecting various parameters such as sea surface temperature (SST), runoff, circulation patterns and the availability of limiting nutrients (like nitrogen, phosphorus and silicon), with each influencing phytoplankton communities differently. This study is based on weekly to fortnightly in vivo fine-spatial-resolution (∼ 1 km) phytoplankton observations along an nearshore–offshore gradient in the French waters of the Eastern English Channel in the Strait of Dover. The phytoplankton functional composition was addressed by automated “pulse-shape recording” flow cytometry, coupled with the analysis of environmental variables over the last decade (2012–2022). This method allows for the characterization of almost the entire phytoplankton size range (from 0.1 to 800 µm width) and the determination of the abundance of functional groups based on optical single-cell signals (fluorescence and scatter). We explored seasonal, spatial and decadal dynamics in an environment strongly influenced by tides and currents. Over the past 11 years, the SST has shown an increasing trend at all stations, with nearshore waters warming faster than offshore waters (+1.05 °C vs. +0.93 °C). Changes in nutrient concentrations have led to imbalances in nutrient ratios (N:P:Si) relative to reference nutrient ratios. However, a return to balanced ratios has been observed since 2019. The phytoplankton total abundance has also increased over the aforementioned decade, with a higher contribution of small-sized cells (picoeukaryotes and picocyanobacteria) and a decrease in microphytoplankton, particularly near the coast. Based on an analysis of environmental parameters and phytoplankton abundance, the winters of 2013–2014 and 2019–2020 were identified as shifting periods in this time series. These changes in the phytoplankton community, favoring the smallest groups, could lead to a reduction in the productivity of coastal marine ecosystems, which could, in turn, affect higher trophic levels and the entire food web.

What threats do Brazilian National parks face? - Alícia Helena Torres da Rocha; Jhonatan Guedes-Santos; Felipe Alexandre Santos Vieira; Ana Claudia Mendes Malhado; Richard J. Ladle; Jairo Lizandro Schmitt; Chiara Bragagnolo (Journal for Nature Conservation, 2025)

Organic matter sources, accumulation and diagenesis of the Lontras Shale Lagerstätte (Paraná Basin, southern Brazil) - Alexandre Ribeiro Cardoso; Jaques Soares Schmidt; Eduardo Müller Bernardes; Anderson José Maraschin; Débora de Coelho Andrade; Filipe de Medeiros Albano; Gabriel Rübensam; Gustavo Bombardelli Barp; Juliana Nichele Kich; Naira Poerner Rodrigues; Yasmin Felix de Oliveira; João Pedro Tauscheck Zielinski; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Mixed models in the selection of interspecific crosses of Psidium spp. resistant to myrtle rust - Letícia da Silva Araújo; Alexandre Pio Viana; Silvaldo Felipe da Silveira; Beatriz Murizini Carvalho; Débora Souza Mendes; Joameson Antunes Lima (European Journal of Plant Pathology, 2025)

Efficiency of different techniques to analyze sperm capacitation in bulls - Laura Nataly Garcia-Oliveros; Alexandre da Rocha Bozzi; Thais de Oliveira Cardoso Silva; Fernanda Baatsch Nascimento; Thainara Rodrigues de Oliveira; Maíra Bianchi Rodrigues Alves; Juliano Coelho da Silveira; Felipe Perecin; Rubens Paes de Arruda; Eneiva Carla Carvalho Celeghini (Animal Reproduction Science, 2025)

Potential of Scenedesmus sp. and Aurantiochytrium spp. as protein and n-3 fatty acid sources in practical diets for juvenile Penaeus vannamei - Alberto J. P. Nunes; Felipe Nobre Façanha; Jordana Sampaio Leite; Alexandre F. Diógenes (Aquaculture International, 2025)

Morphological and cellular effects in Boana faber tadpoles (Anura: Hylidae) exposed to atrazine-based herbicide and glyphosate-based herbicide and their mixtures - Felipe André Pavan; Caroline Garcia Samojeden; Camila Fátima Rutkoski; Alexandre Folador; Silvia Pricila da Fré; Aline Pompermaier; Caroline Müller; Paulo Afonso Hartmann; Marilia Hartmann (Environmental Science and Pollution Research, 2024)

Fluvial erosion in a catchment cultivated with no-tillage at the edge of the southern Brazilian plateau - Felipe Bernardi; Jean P. G. Minella; Alice Prates Bisso Dambroz; Alexandre Schlesner; Gustavo H. Merten; Luca Mao; Olivier Evrard; Daniel Gustavo Allasia Piccilli; Ricardo Simão Dinis Dalmolin; Fabrício de Araújo Pedron (Environmental Monitoring and Assessment, 2024)

Novel beer bitterness measurement instrument using optical fiber sensor - Renato Luiz Faraco Filho; Felipe Oliveira Barino; João Victor Calderano; Deivid Campos; Ítalo Fernandes Valle Alvarenga; André William Paviani Manhas; Alexandre Bessa dos Santos (Journal of Food Engineering, 2024)

Calibrated Eckhardt’s filter versus alternative baseflow separation methods: A silica-based approach in a Brazilian catchment - Fernanda Helfer; Felipe K. Bernardi; Cláudia Alessandra Peixoto de Barros; Daniel Gustavo Allasia Piccilli; Jean Paolo Gomes Minella; Rutinéia Tassi; Alexandre Augusto Schlesner (Journal of Hydrology, 2024)

First geological survey and characterisation of a giant depression in carbonate strata at the Rio Grande Rise (southwestern Atlantic) - Alexandre Henrique Ferraz; Christian Millo; Paulo César Fonseca Giannini; Thales Chamarelli Felipe; André Luiz Silva Pestilho; Lena Virgínia Soares Monteiro; Carina Ulsen; Bramley J. Murton; Luigi Jovane (Geomorphology, 2024)

Effect of access to natural shade on scrotal thermoregulatory capacity, integrity of the testicular parenchyma and sperm morphology of Nelore (Bos indicus) and Canchim (Bos taurus x Bos indicus) bulls - Narian Romanello; Andréa do Nascimento Barreto; Júlio Cesar de Carvalho Balieiro; Felipe Zandonadi Brandão; André Furugen Cesar de Andrade; Martina Zappaterra; Alexandre Rossetto Garcia (International Journal of Biometeorology, 2024)

Methylphenidate Exposing During Neurodevelopment Alters Amino Acid Profile, Astrocyte Marker and Glutamatergic Excitotoxicity in the Rat Striatum - Felipe Schmitz; Luz Elena Durán-Carabali; Alessandra Schmitt Rieder; Josiane S. Silveira; Osmar Vieira Ramires Junior; Larissa D. Bobermin; André Quincozes-Santos; Vinícius S. Alves; Robson Coutinho-Silva; Luiz Eduardo B. Savio; Daniella M. Coelho; Carmen R. Vargas; et al. (Neurotoxicity Research, 2024)

Recurrent selection in Passiflora: a new approach for the development of cowpea aphid-borne mosaic virus resistant cultivars with desired agronomic traits - Débora Souza Mendes; Alexandre Pio Viana; Natan Ramos Cavalcante; Gabriela Tavares Pires; Eileen Azevedo Santos; Flávia Alves da Silva; Felipe Durães do Nascimento Monteiro Barbosa; Letícia da Silva Araújo; Thays Correa Costa; Julie Anne Vieira Salgado de Oliveira; Mariana Quintas Maitan; Nilmária Natália Veras Reis (European Journal of Plant Pathology, 2024)

Integrating Health and Climate Data to Enhance Snakebite Envenomation Response - Joao Vitor Perez de Souza; Alexandre Vilhena da Silva Neto; Marcos Adriano Garcia Campos; Elle Strand; Wuelton Monteiro; Felipe Murta; Jacqueline Sachett; Fan Wen Hui; Brian McAdoo; Charles Gerardo; Joao Ricardo Nickenig Vissoci (Toxicon, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Reproductive, productive and financial consequences of chronic Trypanosoma vivax infection in a dairy cattle herd in a region without a cyclic vector - Luiz Fellipe Monteiro Couto; Thiago Souza Azeredo Bastos; Igor Maciel Lopes de Morais; Vanessa Ferreira Salvador; Luccas Lourenzzo Lima Lins Leal; Ricardo Backstron Falavigna; José Felipe Warmling Spricigo; Rinaldo Aparecido Mota; Breno Cayero Cruz; Marcos Henrique Alcantara Colli; Alexandre Braga Scarpa; Vando Edesio Soares; et al. (Veterinary Parasitology, 2024)

Ten years of directing seeding restoration in the Brazilian savanna: Lessons learned and the way forward - Ana Wiederhecker; Maxmiller Cardoso Ferreira; Silvia Barbosa Rodrigues; Alexandre Bonesso Sampaio; Isabel Belloni Schmidt; José Felipe Ribeiro; Roberto Shojirou Ogata; Maísa Isabela Rodrigues; Augusto Cesar Silva-Coelho; Icaro Sousa Abreu; Thaís Franco Montenegro; Daniel Luis Mascia Vieira (Journal of Environmental Management, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Do invasive and native grasses in Brazilian Savanna differ in their photosynthetic performance under natural light radiation? - Áurea Rodrigues Cordeiro; Alexandre Aparecido Duarte; Felipe Della-Torre; Fernando Afonso Nonato França; Marcel Giovanni Costa França (Flora, 2024)

Carbon and nitrogen, humic and labile fractions in soil under clonal eucalyptus stands from cerrado - Wendel dos Santos Moraes; Luiz Fernandes Silva Dionisio; Gustavo Schwartz; Juliana Andrade Pereira; Jossimara Ferreira Damascena; Felipe Alexandre Rizzo; Alberto Bentes Brasil Neto; Camila de Almeida Milhomem; José Maria Arcanjo Alves; Renisson Neponuceno Araujo Filho; Renato de Almeida Sarmento; Alinne da Silva; et al. (European Journal of Forest Research, 2024)

Shifts in microbiota and gene expression of nutrient transporters, mucin and interleukins in the gut of fast-growing and slow-growing chickens infected by Salmonella Enteritidis - Maylane Rayane Brito dos Santos; Alexandre Lemos de Barros Moreira Filho; Oliveiro Caetano Freitas Neto; Maria de Fátima de Souza Andrade; Núbia Michelle Vieira da Silva; Gustavo Felipe Correia Sales; Celso José Bruno de Oliveira; Patrícia Emília Naves Givisiez (Brazilian Journal of Microbiology, 2024)

Anaplasmosis outbreaks in taurine and zebu cattle in Brazil: causes, treatments, and Anaplasma marginale genetic diversity - Luccas Lourenzzo Lima Lins Leal; Alliny Souza de Assis Cavalcante; Igor Maciel Lopes de Moraes; Vanessa Salvador; Luiz Fellipe Monteiro Couto; Luciana Maffini Heller; Dina Maria Beltrán Zapa; Warley Vieira de Freitas Paula; Kamila Gaudêncio da Silva Sales; Eduardo Lima; Alexandre Braga Scarpa; Ricardo Antônio Amaral de Lemos; et al. (Tropical Animal Health and Production, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Local attitudes towards conservation governance in a large tropical multiple-use Marine Protected Area in Brazil - José Gilmar Cavalcante de Oliveira Júnior; Ana Paula de Oliveira Santos; Ana Claudia Mendes Malhado; Carolina Neves Souza; Chiara Bragagnolo; Aline Olímpio dos Santos; Evelynne Letícia dos Santos Farias Cardoso de Barros; Felipe Alexandre Santos Vieira; Inaê Farias Vieira Dantas; Jacqueline Costa Aldabalde; João Vitor Campos-Silva; Johnny Antonio da Silva Lima; et al. (Ocean & Coastal Management, 2024)

The interplay between Azospirillum brasilense and the native bacterial communities in the soil and rhizosphere of maize (Zea mays L.) - Alexandre Pedrinho; Lucas William Mendes; Felipe Martins do Rêgo Barros; João William Bossolani; Tayná Negri Kühn; Maria Carolina Quecine; Fernando Dini Andreote (Soil Biology and Biochemistry, 2024)

Deciphering recycling processes during solar system evolution from magnesium-rich relict olivine grains in type II chondrules - Gabriel A. Pinto; Emmanuel Jacquet; Alexandre Corgne; Felipe Olivares; Johan Villeneuve; Yves Marrocchi (Geochimica et Cosmochimica Acta, 2024)

Copper and silver nanoparticles control coffee rust: decrease the quantity of sprayed active ingredients and is an alternative for sustainable coffee production - Felipe Douglas Soares Leal; Helon Santos Neto; Indiara Carol Lopes Pinheiro; Julia Marques Oliveira; Adélia Aziz Alexandre Pozza; Edson Ampélio Pozza (European Journal of Plant Pathology, 2024)

Envirotype approach for soybean genotype selection through the integration of georeferenced climate and genetic data using artificial neural networks - Bruno Grespan Leichtweis; Letícia de Faria Silva; Marco Antônio Peixoto; Luiz Alexandre Peternelli; Felipe Lopes da Silva (Euphytica, 2024)

Presence and ecotoxicity of residual antidepressants in environmental samples - Patrícia Alexandre Evangelista; Franz Zirena Vilca; Rodrigo Floriano Pimpinato; Fernando Periotto; Felipe Machado de Oliveira Lourenço; Valdemar Luiz Tornisielo (Environmental Nanotechnology, Monitoring & Management, 2023)

Bumetanide Attenuates Cognitive Deficits and Brain Damage in Rats Subjected to Hypoxia–Ischemia at Two Time Points of the Early Postnatal Period - Diorlon Nunes Machado; Luz Elena Durán-Carabali; Felipe Kawa Odorcyk; Andrey Vinicios Soares Carvalho; Ana Paula Rodrigues Martini; Livia Machado Schlemmer; Marcel de Medeiros de Mattos; Gabriel Pereira Bernd; Carla Dalmaz; Carlos Alexandre Netto (Neurotoxicity Research, 2023)

Constructing high-resolution stratigraphic frameworks by the application of signal analysis techniques: Example of Balbuena IV sequence, Yacoraite formation, Salta Basin - José Arthur Oliveira Santos; Alexandre Uhlein; Márcio Dantas; Gabriel de Morais Coutinho; Thomás Jung Spier; Kaio Henrique Masse Vieira; Alan Cabral Trindade Prado; Douglas Macharet; Gabriel Jubé Uhlein; Tiago Novo; Humberto Reis; Felipe Alves Farias; et al. (Marine and Petroleum Geology, 2023)

Effects of experimental ulcerative colitis on myenteric neurons in P2X7-knockout mice - Felipe Alexandre Machado; Roberta Figueiroa Souza; Vanessa Ribeiro Figliuolo; Robson Coutinho-Silva; Patricia Castelucci (Histochemistry and Cell Biology, 2023)

Plant-parasitic nematode community and enzyme activities in soils under no-till soybean crops in Brazil - Felipe Martins do Rêgo Barros; Alexandre Pedrinho; Gustavo da Cunha Sant’Ana; Caio César Gomes Freitas; Juliana Magrinelli Osório Rosa; Claudio Marcelo Gonçalves de Oliveira; Caique Rozada; Felipe Nogueira de Sá Marto; João Augusto Lopes Pascoalino; Luiz Antônio da Silva; Fernando Dini Andreote (Rhizosphere, 2023)

Landscape Genetics for Brazilian Equines - Felipe Pimentel; Concepta McManus; Kaifer Soares; Alexandre Rodrigues Caetano; Danielle Assis de Faria; Samuel Rezende Paiva; Patrícia Ianella (Journal of Equine Veterinary Science, 2023)

Thermal comfort of Nelore (Bos indicus) and Canchim (Bos taurus x Bos indicus) bulls kept in an integrated crop-livestock-forestry system in a tropical climate - Narian Romanello; Andréa do Nascimento Barreto; Marco Antonio Paula de Sousa; Júlio Cesar de Carvalho Balieiro; Felipe Zandonadi Brandão; Felipe Tonato; Alberto Carlos de Campos Bernardi; José Ricardo Macedo Pezzopane; José Alberto Bastos Portugal; Alexandre Rossetto Garcia (Agricultural Systems, 2023)

Genotoxic effects of anthropogenic environments in the leaf litter-dwelling scorpion Tityus pusillus Pocock, 1893 (Scorpiones; Buthidae) - Aleson Aparecido da Silva; Érima Maria de Amorim; Maria Gislaine Pereira; Samuel Lima de Santana; Meykson Alexandre da Silva; André Felipe de Araujo Lira; Claudia Rohde (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Correction: Genetic differentiation pattern and evidence of an early speciation process in the genus Reithrodon (Rodentia: Sigmodontinae) - Heloisa Allgayer; Alexandre Uarth Christoff; Felipe Bortolotto Peters; Paulo Ricardo de Oliveira Roth; Márcia Maria de Assis Jardim; Victor Hugo Valiati (Mammalian Biology, 2023)

Genetic differentiation pattern and evidence of an early speciation process in the genus Reithrodon (Rodentia: Sigmodontinae) - Heloisa Allgayer; Alexandre Uarth Christoff; Felipe Bortolotto Peters; Paulo Ricardo de Oliveira Roth; Márcia Maria de Assis Jardim; Victor Hugo Valiati (Mammalian Biology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Physiological, epigenetic, and proteomic responses in Pfaffia glomerata growth in vitro under salt stress and 5-azacytidine - Evandro Alexandre Fortini; Diego Silva Batista; Sérgio Heitor Sousa Felipe; Tatiane Dulcineia Silva; Ludmila Nayara Freitas Correia; Letícia Monteiro Farias; Daniele Vidal Faria; Vitor Batista Pinto; Claudete Santa-Catarina; Vanildo Silveira; Clelia De-la-Peña; Eduardo Castillo-Castro; et al. (Protoplasma, 2023)

Sugarcane yeast with urea in replace of soybean meal in the diet of Murrah buffaloes does not cause metabolic, endocrine, and mineral disorders - Bruna Higino de Souza Silva; Rebeka Menezes Pontes; Ayna Arramis Apolinário da Silva; Esdras Lima de Carvalho Gueiros; Emanuel Felipe de Oliveira Filho; Daniel da Silva Praia; Daniel Nunes de Araújo Gonçalves; Tomás Guilherme Pereira da Silva; Ricardo Alexandre Silva Pessoa; Cláudio Coutinho Bartolomeu; Pierre Castro Soares (Tropical Animal Health and Production, 2023)

Mangrove microbial community recovery and their role in early stages of forest recolonization within shrimp ponds - Miguel Loiola; Amaro Emiliano Trindade Silva; Marcos Krull; Felipe Alexandre Barbosa; Eduardo Henrique Galvão; Vinicius F. Patire; Igor Cristino Silva Cruz; Francisco Barros; Vanessa Hatje; Pedro Milet Meirelles (Science of The Total Environment, 2023)

Screening of new adsorbents to remove algal organic matter from aqueous solutions: kinetic analyses and reduction of disinfection by-products formation - Luan de Souza Leite; Maria Teresa Hoffmann; Fábio Simões de Vicente; Danilo Vitorino dos Santos; Alexandre Mesquita; Felipe Bonganhi Juliato; Luiz Antonio Daniel (Environmental Science and Pollution Research, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

The addition of different oils in the diet regulates the expression of adipocytokine signaling genes in sheep longissimus dorsi muscle - Paulo Henrique Souza; Edwana Mara Moreira Monteiro; Elizabeth Machado Barbosa; Alexandre Rosário Casseb; Wilson Amaro Conde Moreira Sobrinho; Felipe Nogueira Domingues; Cristian Faturi; Aníbal Coutinho Rêgo; Ednaldo Silva Filho (Tropical Animal Health and Production, 2022)

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Inter-sectoral prioritization of climate technologies: insights from a Technology Needs Assessment for mitigation in Brazil - Fábio T. F. da Silva; Alexandre Szklo; Amanda Vinhoza; Ana Célia Nogueira; André F. P. Lucena; Antônio Marcos Mendonça; Camilla Marcolino; Felipe Nunes; Francielle M. Carvalho; Isabela Tagomori; Laura Soares; Márcio Rojas da Cruz; et al. (Mitigation and Adaptation Strategies for Global Change, 2022)

Environmental stratification in trials of unbalanced multiyear soybean (Glycine max (l.) Merril) via the integration of GGE Biplot graphs and networks of environmental similarity - Fernanda Cupertino Rodrigues; Francisco Charles Santos Silva; Pedro Crescêncio Souza Carneiro; Luiz Alexandre Peternelli; Leonardo Lopes Bhering; Felipe Lopes da Silva (Euphytica, 2022)

Oil Spill and Socioeconomic Vulnerability in Marine Protected Areas - Felipe Roberto da Silva; Alexandre Schiavetti; Ana Cláudia Mendes Malhado; Beatrice Ferreira; Caio Victor de Paula Sousa; Fábio Pessoa Vieira; Francisco Roberto Pinto; Gabriel Barros Gonçalves de Souza; George Olavo; Jéssica Borba Quintela dos Santos; Joao Vitor Campos-Silva; José Gilmar Cavalcante de Oliveira Júnior; et al. (Frontiers in Marine Science, 2022)
The extensive oil spill (> 2,900 km) that occurred in the southwestern Atlantic (2019/2020) increased the vulnerability of the Brazilian coast, affecting marine and coastal protected areas (MPAs). In addition to supporting conservation, MPAs are sustainably used by local populations to help maintain ocean-dependent livelihoods. In this sense, we aim to assess the socioeconomic vulnerability of human communities in MPAs affected by this major oil spill. Using digital mapping, we assessed the socioeconomic vulnerability of 68 human communities living in or near 60 MPAs of different categories that were impacted by this spill. This is the first assessment of the vulnerability status of human populations under significant levels of poverty and social inequality, which are particularly dependent on healthy and effective Brazilian MPAs. More than 6,500 enterprises and institutions were mapped, including trade activities, services, tourism, and leisure venues. Most enterprises (34.4%) were involved in the food sector, related to the ocean economy, and, therefore, highly vulnerable to oil spills. Furthermore, the majority (79.3%) of the vulnerable activities are concentrated in multiple-use MPAs, with extractive reserves coming second and accounting for 18%. This result shows the high vulnerability of this tropical coast to oil accidents and the risks to food security for traditional communities. We also found a heterogeneous vulnerability indicator along the coast, with the most vulnerable regions having an undiversified economic matrix heavily dependent on activities such as fishing, family farming, tourism, accommodation, and the food sector. Thus, this study provides a tool to help prevent and mitigate economic losses and increases the understanding of the weaknesses of MPAs in the face of large-scale disasters, thus helping to build socioeconomic and ecological resilience.

New records of the occurrence of biting midges (Diptera: Ceratopogonidae) species in rural area of Santa Maria, Rio Grande do Sul, in the South of Brazil - Julia Somavilla Lignon; Emanuelle de Souza Farias; Felipe Arley Costa Pessoa; Eduarda Maria Trentin Santi; Lucas Alexandre Farias de Souza; Gilneia da Rosa; Diego Moscarelli Pinto; Luciana Pötter; Silvia Gonzalez Monteiro (International Journal of Tropical Insect Science, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Benthic Cyanobacterial Diversity and Antagonistic Interactions in Abrolhos Bank: Allelopathy, Susceptibility to Herbivory, and Toxicity - Felipe de Vargas Ribeiro; Taiara Aguiar Caires; Marcela Alvarenga de Almeida Simões; Paulo Iiboshi Hargreaves; Livia Bonetti Villela; Giovana de Oliveira Fistarol; Alexandre Brauns Cazelgrandi; Guilherme Henrique Pereira-Filho; Rodrigo Leão de Moura; Renato Crespo Pereira; Paulo Sergio Salomon (Frontiers in Marine Science, 2022)
Benthic cyanobacterial mats (BCMs) are conspicuous components of coral reef communities, where they play key ecological roles as primary producers among others. BCMs often bloom and might outcompete neighboring benthic organisms, including reef-building corals. We investigated the cyanobacterial species composition of three BCMs morphotypes from the marginal reef complex of Abrolhos Bank (Southeastern Brazil). Also, we assessed their allelopathic effects on coral zooxanthellae, their susceptibility to herbivory by fish, and their toxicity to brine shrimp nauplii. Morphology and 16S rDNA sequencing unveiled the cyanobacteria Moorena bouillonii , Okeania erythroflocculosa , Adonisia turfae , Leptolyngbya sp., and Halomicronema sp. as components of BCMs from Abrolhos. BCMs cell-free filtrates and extracts exerted an allelopathic effect by reducing the growth of the ex hospite Symbiodinium sp. in culture. BCMs-only treatments remained untouched in field susceptibility assays in contrast to macroalgae only and mixed BCMs-macroalgae treatments that had the macroalgae fully removed by reef fish. Crude aqueous extracts from BCMs were toxic to brine shrimps in acute assays. Besides unveiling the diversity of BCMs consortia in Abrolhos, our results cast some light on their allelopathy, antiherbivory, and toxicity properties. These antagonistic interactions might promote adverse cascading effects during benthic cyanobacteria blooms and in gradual shifts to BCMs-dominated states.

Dereplication and evaluation of the antinociceptive and anti-inflammatory activity of hydroethanolic extract of leaves from Campomanesia xanthocarpa O. Berg - Fabrício Damasceno Leandro; Layla Dutra Marinho Cabral; Tallita Marques Machado; Hector Henrique Ferreira Koolen; Felipe Moura Araújo da Silva; Fernanda Guilhon-Simplicio; Marcelo Aparecido da Silva; Alexandre Giusti-Paiva; Clarice de Carvalho Veloso Moura; Geraldo Alves da Silva (Natural Product Research, 2021)

Unmanned aerial vehicle to evaluate frost damage in coffee plants - Diego Bedin Marin; Gabriel Araújo e Silva Ferraz; Felipe Schwerz; Rafael Alexandre Pena Barata; Rafael de Oliveira Faria; Jessica Ellen Lima Dias (Precision Agriculture, 2021)

Diagnosis of Systemic Diseases Using Infrared Spectroscopy: Detection of Iron Overload in Plasma—Preliminary Study - Leonardo Barbosa Leal; Marcelo Saito Nogueira; Jandinay Gonzaga Alexandre Mageski; Thiago Pereira Martini; Valério Garrone Barauna; Leonardo dos Santos; Luis Felipe das Chagas e Silva de Carvalho (Biological Trace Element Research, 2021)

Regulatory approaches for genome edited agricultural plants in select countries and jurisdictions around the world - Jon Entine; Maria Sueli S. Felipe; Jan-Hendrik Groenewald; Drew L. Kershen; Martin Lema; Alan McHughen; Alexandre Lima Nepomuceno; Ryo Ohsawa; Reynante L. Ordonio; Wayne A. Parrott; Hector Quemada; Carl Ramage; et al. (Transgenic Research, 2021)
Genome editing in agriculture and food is leading to new, improved crops and other products. Depending on the regulatory approach taken in each country or region, commercialization of these crops and products may or may not require approval from the respective regulatory authorities. This paper describes the regulatory landscape governing genome edited agriculture and food products in a selection of countries and regions.

Quantitative genetics of extreme insular dwarfing: The case of red deer on Jersey - José Alexandre F. Diniz‐Filho; Ana M. C. Santos; Elisa Barreto; Felipe Naves; Wanderson Santos; Kelly Silva Souza; Rejane Santos‐Silva; Ricardo Dobrovolski; Thannya Nascimento Soares; Rosana Tidon; Zander Augusto Spigoloni; Thiago F. Rangel; et al. (Journal of Biogeography, 2021)
Aim The Island Rule—that is, the tendency for body size to decrease in large mammals and increase in small mammals on islands has been commonly evaluated through macroecological or macroevolutionary, pattern‐orientated approaches, which generally fail to model the microevolutionary processes driving either dwarfing or gigantism. Here, we seek to identify which microevolutionary process could have driven extreme insular dwarfism in the extinct dwarf red deer population on the island of Jersey. Location Jersey, UK (Channel Islands). Taxon Red deer ( Cervus elaphus ). Methods We applied an individual‐based quantitative genetics model parameterized with red deer life‐history data to study the evolution of dwarfism in Jersey's deer, considering variations in island area and isolation through time due to sea level changes. Results The body size of red deer on Jersey decreased fast early on, due to phenotypic plasticity, then kept decreasing almost linearly over time down to the actual body size of the Jersey deer (36 kg on average). Only 1% of 10,000 replicates failed to reach that size in our simulations. The distribution of time to adaptation in these simulations was right skewed, with a median of 395 generations (equivalent to roughly 4 kyr), with complete dwarfism effectively occurring in less than 6 kyr 84.6% of times. About 72% of the variation in the time to adaptation between simulations was collectively explained by higher mutational variance, the number of immigrants from the continent after isolation, available genetic variance, heritability, and phenotypic plasticity. Main Conclusions The extreme dwarfing of red deer on Jersey is an expected outcome of high mutational variance, high immigration rate, a wide adaptive landscape, low levels of inbreeding, and high phenotypic plasticity (in the early phase of dwarfing), all occurring within a time window of around 6 kyr. Our model reveals how extreme dwarfism is a plausible outcome of common, well‐known evolutionary processes.

Novelties in Lactifluus subg. Gymnocarpi (Russulales, Basidiomycota) from Brazilian tropical forests - Alexandre G. S. Silva-Filho; Mariana C. A. Sá; Dirce L. Komura; Iuri G. Baseia; Paulo Marinho; Jean-Marc Moncalvo; Mélanie Roy; Felipe Wartchow (Mycological Progress, 2021)

Gas exchange rates and sucrose concentrations affect plant growth and production of flavonoids in Vernonia condensata grown in vitro - Evandro Alexandre Fortini; Diego Silva Batista; Talita Cristina Mamedes-Rodrigues; Sérgio Heitor Sousa Felipe; Ludmila Nayara Freitas Correia; Kristhiano Chagas; Priscila Oliveira Silva; Diego Ismael Rocha; Wagner Campos Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Irradiance-driven 20-hydroxyecdysone production and morphophysiological changes in Pfaffia glomerata plants grown in vitro - Tatiane Dulcineia Silva; Diego Silva Batista; Kamila Motta Castro; Evandro Alexandre Fortini; Sérgio Heitor Sousa Felipe; Amanda Mendes Fernandes; Raysa Mayara Jesus Sousa; Kristhiano Chagas; José Victor Siqueira da Silva; Ludmila Nayara Freitas Correia; Gabriela Torres-Silva; Letícia Monteiro Farias; et al. (Protoplasma, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Identification and characterization of Sinuolinea niloticus from Nile tilapia (Oreochromis niloticus) farmed in Botucatu, Brazil - Alexandre Battazza; Felipe César da Silva Brasileiro; Eduardo Ferreira Machado; Magna Gomes de Matos; Cauê Bastos Tertuliano dos Santos; Marianna Vaz Rodrigues; Diana do Nascimento; Noeme Sousa Rocha (Aquaculture International, 2020)

Photoperiod modulates growth and pigments and 20-hydroxyecdysone accumulation in Brazilian ginseng [Pfaffia glomerata (Spreng.) Pedersen] grown in vitro - Evandro Alexandre Fortini; Diego Silva Batista; Kamila Motta de Castro; Tatiane Dulcineia Silva; Sérgio Heitor Sousa Felipe; Ludmila Nayara Freitas Correia; Kristhiano Chagas; Letícia Monteiro Farias; João Paulo Viana Leite; Wagner Campos Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Assessing drought in the drylands of northeast Brazil under regional warming exceeding 4 °C - Jose A. Marengo; Ana Paula M. A. Cunha; Carlos A. Nobre; Germano G. Ribeiro Neto; Antonio R. Magalhaes; Roger R. Torres; Gilvan Sampaio; Felipe Alexandre; Lincoln M. Alves; Luz A. Cuartas; Karinne R. L. Deusdará; Regina C. S. Álvala (Natural Hazards, 2020)

Water deficit modulates growth, morphology, and the essential oil profile in Lippia alba L. (Verbenaceae) grown in vitro - Kamila Motta de Castro; Diego Silva Batista; Tatiane Dulcineia Silva; Evandro Alexandre Fortini; Sérgio Heitor Sousa Felipe; Amanda Mendes Fernandes; Raysa Mayara de Jesus Sousa; Laís Stehling de Queiroz Nascimento; Victória Rabelo Campos; Richard Michael Grazul; Lyderson Facio Viccini; Wagner Campos Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

CRISPR, Prime Editing, Optogenetics, and DREADDs: New Therapeutic Approaches Provided by Emerging Technologies in the Treatment of Spinal Cord Injury - Vera Paschon; Felipe Fernandes Correia; Beatriz Cintra Morena; Victor Allisson da Silva; Gustavo Bispo dos Santos; Maria Cristina Carlan da Silva; Alexandre Fogaça Cristante; Stephanie Michelle Willerth; Florence Evelyne Perrin; Alexandre Hiroaki Kihara (Molecular Neurobiology, 2020)

Salinity modulates growth, morphology, and essential oil profile in Lippia alba L. (Verbenaceae) grown in vitro - Kamila Motta de Castro; Diego Silva Batista; Tatiane Dulcineia Silva; Evandro Alexandre Fortini; Sérgio Heitor Sousa Felipe; Amanda Mendes Fernandes; Raysa Mayara de Jesus Sousa; Laís Stehling de Queiroz Nascimento; Victória Rabelo Campos; Lyderson Facio Viccini; Richard Michael Grazul; Wagner Campos Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Unraveling Deep Branches of the Sigmodontinae Tree (Rodentia: Cricetidae) in Eastern South America - Pablo R. Gonçalves; Alexandre U. Christoff; Leonardo F. Machado; Cibele R. Bonvicino; Felipe B. Peters; Alexandre R. Percequillo (Journal of Mammalian Evolution, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Hygrocybe aurantiomagnifica: a new species of section Firmae (Hygrophoraceae, Basidiomycota) from Brazil - Alexandre G. S. Silva-Filho; Angelina Meiras-Ottoni; Felipe Wartchow (Kew Bulletin, 2019)

Type studies and new combinations in Brazilian milkcaps ( Lactifluus , Russulaceae) - Alexandre G. S. Silva‐Filho; Felipe Wartchow (New Zealand Journal of Botany, 2019)
In the tropics, the diversity of ectomycorrhizal milkcaps is predominantly represented by genus Lactifluus . In Brazil, species traditionally described as Lactarius need to be revised and recombined. Thus, seven milkcaps from Amazonia and Rio Grande do Sul, Brazil, published by Rick, Singer and co‐authors were reviewed. Lactarius amazonensis , L. brasiliensis , L. braunii , L. mamorensis and L. russula , along with the recently described L. rupestris , are combined in Lactifluus . In addition, Lactifluus annulifer together with Lf. braunii and Lf. russula , have lectotypes designated. A modern and detailed microscopic description, drawings and taxonomic discussion are provided for each species.

Productive performance and reproductive characteristics of Morada Nova male lambs fed with high-energy diet - Andréa do Nascimento Barreto; André Guimarães Maciel e Silva; Sergio Novita Esteves; Manuel Antonio Chagas Jacinto; Waldomiro Barioni Junior; Felipe Zandonadi Brandão; Messy Hannear de Andrade Pantoja; Daniela Botta; Narian Romanello; Amanda Prudêncio Lemes; Alessandro Giro; Alexandre Rossetto Garcia (Tropical Animal Health and Production, 2019)

Revisiting the crop coefficient–reference evapotranspiration procedure for improving irrigation management - Fábio R. Marin; Luiz R. Angelocci; Daniel S. P. Nassif; Murilo S. Vianna; Felipe G. Pilau; Evandro H. F. M. da Silva; Luiz R. Sobenko; Alexandre O. Gonçalves; Rodolfo A. A. Pereira; Kassio S. Carvalho (Theoretical and Applied Climatology, 2019)

Accessions of Brazilian ginseng (Pfaffia glomerata) with contrasting anthocyanin content behave differently in growth, antioxidative defense, and 20-hydroxyecdysone levels under UV-B radiation - Sérgio Heitor Sousa Felipe; Diego Silva Batista; Kristhiano Chagas; Ludmila Nayara Freitas Correia; Tatiane Dulcineia Silva; Evandro Alexandre Fortini; Priscila Oliveira Silva; Wagner Campos Otoni (Protoplasma, 2019)

Effects of surface pre-reacted glass-ionomer (S-PRG) eluate on Candida spp.: antifungal activity, anti-biofilm properties, and protective effects on Galleria mellonella against C. albicans infection - Rodnei Dennis Rossoni; Patrícia Pimentel de Barros; Lucas Alexandre das Chagas Lopes; Felipe Camargo Ribeiro; Toshiyuki Nakatsuka; Hideto Kasaba; Juliana Campos Junqueira (Biofouling, 2019)

Photoperiod modulates growth, morphoanatomy, and linalool content in Lippia alba L. (Verbenaceae) cultured in vitro - Kamila Motta de Castro; Diego Silva Batista; Evandro Alexandre Fortini; Tatiane Dulcineia Silva; Sérgio Heitor Sousa Felipe; Amanda Mendes Fernandes; Raysa Mayara de Jesus Sousa; Laís Stehling de Queiroz Nascimento; Victória Rabelo Campos; Richard Michael Grazul; Lyderson Facio Viccini; Wagner Campos Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Reference gene selection for qRT-PCR in Brazilian-ginseng [Pfaffia glomerata (Spreng.) Pedersen] as affected by various abiotic factors - Diego Silva Batista; Viviane Santos Moreira; Sergio Heitor Sousa Felipe; Evandro Alexandre Fortini; Tatiane Dulcineia Silva; Kristhiano Chagas; Eliza Louback; Elisson Romanel; Marcio Gilberto Cardoso Costa; Wagner Campos Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Milk production and composition, food consumption, and energy balance of postpartum crossbred Holstein-Gir dairy cows fed two diets of different energy levels - Gustavo Bervian dos Santos; Felipe Zandonadi Brandão; Lilian dos Santos Ribeiro; Alexandre Lima Ferreira; Mariana Magalhães Campos; Fernanda Samarini Machado; Bruno Campos de Carvalho (Tropical Animal Health and Production, 2019)

Correction to: Stem Cells from Human Exfoliated Deciduous Teeth Modulate Early Astrocyte Response after Spinal Cord Contusion - Fabrício Nicola; Marília Rossato Marques; Felipe Odorcyk; Letícia Petenuzzo; Dirceu Aristimunha; Adriana Vizuete; Eduardo Farias Sanches; Daniela Pavulack Pereira; Natasha Maurmann; Carlos-Alberto Gonçalves; Patricia Pranke; Carlos Alexandre Netto (Molecular Neurobiology, 2019)

Stem Cells from Human Exfoliated Deciduous Teeth Modulate Early Astrocyte Response after Spinal Cord Contusion - Fabrício Nicola; Marília Rossato Marques; Felipe Odorcyk; Letícia Petenuzzo; Dirceu Aristimunha; Adriana Vizuete; Eduardo Farias Sanches; Daniela Pavulack Pereira; Natasha Maurmann; Carlos-Alberto Gonçalves; Patricia Pranke; Carlos Alexandre Netto (Molecular Neurobiology, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Thermoregulatory responses and reproductive traits in composite beef bulls raised in a tropical climate - Narian Romanello; José de Brito Lourenço Junior; Waldomiro Barioni Junior; Felipe Zandonadi Brandão; Cintia Righetti Marcondes; José Ricardo Macedo Pezzopane; Messy Hannear de Andrade Pantoja; Daniela Botta; Alessandro Giro; Ana Beatriz Bossois Moura; Andréa do Nascimento Barreto; Alexandre Rossetto Garcia (International Journal of Biometeorology, 2018)

Synergistic Toxicity of the Neurometabolites Quinolinic Acid and Homocysteine in Cortical Neurons and Astrocytes: Implications in Alzheimer’s Disease - Paula Pierozan; Helena Biasibetti-Brendler; Felipe Schmitz; Fernanda Ferreira; Carlos Alexandre Netto; Angela T. S. Wyse (Neurotoxicity Research, 2018)

Light quality in plant tissue culture: does it matter? - Diego Silva Batista; Sergio Heitor Sousa Felipe; Tatiane Dulcineia Silva; Kamila Motta de Castro; Talita Cristina Mamedes-Rodrigues; Natane Amaral Miranda; Anyela Marcela Ríos-Ríos; Daniele Vidal Faria; Evandro Alexandre Fortini; Kristhiano Chagas; Gabriela Torres-Silva; Aloisio Xavier; et al. (In Vitro Cellular & Developmental Biology - Plant, 2018)

Characterization of multiple antilisterial peptides produced by sakacin P-producing Lactobacillus sakei subsp. sakei 2a - Kátia G. Carvalho; Felipe H. S. Bambirra; Jacques R. Nicoli; Jamil S. Oliveira; Alexandre M. C. Santos; Marcelo P. Bemquerer; Antonio Miranda; Bernadette D. G. M. Franco (Archives of Microbiology, 2018)

Evaluation of Possible Consequences of Zika Virus Infection in the Developing Nervous System - Lais Takata Walter; Guilherme Shigueto Vilar Higa; Juliane Midori Ikebara; Danila Vedovello; Felipe Scassi Salvador; Silvia Honda Takada; Erika Reime Kinjo; Benjamin J. Whalley; Márcia Aparecida Sperança; Alexandre Hiroaki Kihara (Molecular Neurobiology, 2018)

Neonatal hyperglycemia induces cell death in the rat brain - Andrea Pereira Rosa; Caroline Paula Mescka; Felipe Maciel Catarino; Alexandre Luz de Castro; Rayane Brinck Teixeira; Cristina Campos; Guilherme Baldo; Débora Dalmas Graf; Angela de Mattos-Dutra; Carlos Severo Dutra-Filho; Alex Sander da Rosa Araujo (Metabolic Brain Disease, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

ATLANTIC BIRDS : a data set of bird species from the Brazilian Atlantic Forest - Érica Hasui; Jean Paul Metzger; Rafael G. Pimentel; Luís Fábio Silveira; Alex A. d. A. Bovo; Alexandre C. Martensen; Alexandre Uezu; André L. Regolin; Arthur Â. Bispo de Oliveira; Cassiano A. F. R. Gatto; Charles Duca; Christian B. Andretti; et al. (Ecology, 2018)
South America holds 30% of the world's avifauna, with the Atlantic Forest representing one of the richest regions of the Neotropics. Here we have compiled a data set on Brazilian Atlantic Forest bird occurrence (150,423) and abundance samples ( N = 832 bird species; 33,119 bird individuals) using multiple methods, including qualitative surveys, mist nets, point counts, and line transects). We used four main sources of data: museum collections, on‐line databases, literature sources, and unpublished reports. The data set comprises 4,122 localities and data from 1815 to 2017. Most studies were conducted in the Florestas de Interior (1,510 localities) and Serra do Mar (1,280 localities) biogeographic sub‐regions. Considering the three main quantitative methods (mist net, point count, and line transect), we compiled abundance data for 745 species in 576 communities. In the data set, the most frequent species were Basileuterus culicivorus , Cyclaris gujanensis , and Conophaga lineata . There were 71 singletons, such as Lipaugus conditus and Calyptura cristata . We suggest that this small number of records reinforces the critical situation of these taxa in the Atlantic Forest. The information provided in this data set can be used for macroecological studies and to foster conservation strategies in this biodiversity hotspot. No copyright restrictions are associated with the data set. Please cite this Data Paper if data are used in publications and teaching events.

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Effects of fibre digestibility and level of roughage on performance and rumen fermentation of finishing beef cattle - Dannylo Oliveira Sousa; Bruno de Sousa Mesquita; Alexandre Vaz Pires; Miguel Henrique de Almeida Santana; Luis Felipe Prada Silva (Tropical Animal Health and Production, 2017)

“Cerrado” restoration by direct seeding: field establishment and initial growth of 75 trees, shrubs and grass species - Keiko Fueta Pellizzaro; Alba O. O. Cordeiro; Monique Alves; Camila P. Motta; Gustavo M. Rezende; Raissa R. P. Silva; José Felipe Ribeiro; Alexandre B. Sampaio; Daniel L. M. Vieira; Isabel B. Schmidt (Brazilian Journal of Botany, 2017)

D-Galactose Causes Motor Coordination Impairment, and Histological and Biochemical Changes in the Cerebellum of Rats - André Felipe Rodrigues; Helena Biasibetti; Bruna Stela Zanotto; Eduardo Farias Sanches; Felipe Schmitz; Vinícius Tejada Nunes; Paula Pierozan; Vanusa Manfredini; Débora Delwing Dal Magro; Carlos Alexandre Netto; Angela T.S. Wyse (Molecular Neurobiology, 2017)

Synthesis of piplartine analogs and preliminary findings on structure–antimicrobial activity relationship - Antonio Maciel Fregnan; Guilherme Andrade Brancaglion; Alexandre Francisco Cerqueira Galvão; Cinara Oliveira D’Sousa Costa; Diogo Rodrigo Magalhães Moreira; Milena Botelho Pereira Soares; Daniel Pereira Bezerra; Naiara Chaves Silva; Stella Maria de Souza Morais; Josidel Conceição Oliver; Amanda Latercia Tranches Dias; Luiz Felipe Leomil Coelho; et al. (Medicinal Chemistry Research, 2017)

Horizontal study of vaccinia virus infections in an endemic area: epidemiologic, phylogenetic and economic aspects - Felipe L. Assis; Ana Paula M. Franco-Luiz; Luis M. Paim; Graziele P. Oliveira; Alexandre F. Pereira; Gabriel M. F. de Almeida; Leandra B. Figueiredo; Adriano Tanus; Giliane S. Trindade; Paulo P. Ferreira; Erna G. Kroon; Jônatas S. Abrahão (Archives of Virology, 2015)

Exogenously induced brain activation regulates neuronal activity by top-down modulation: conceptualized model for electrical brain stimulation - Lauren Naomi Spezia Adachi; Alexandre Silva Quevedo; Andressa de Souza; Vanessa Leal Scarabelot; Joanna Ripoll Rozisky; Carla de Oliveira; Paulo Ricardo Marques Filho; Liciane Fernandes Medeiros; Felipe Fregni; Wolnei Caumo; Iraci L. S. Torres (Experimental Brain Research, 2015)

Germline CDKN2A mutations in Brazilian patients of hereditary cutaneous melanoma - Alexandre Leon Ribeiro de Ávila; Ana Cristina Victorino Krepischi; Luciana Facure Moredo; Talita Ferreira Marques Aguiar; Felipe Carneiro da Silva; Bianca Costa Soares de Sá; Amanda França de Nóbrega; Maria Isabel Waddington Achatz; João Pedreira Duprat; Gilles Landman; Dirce Maria Carraro (Familial Cancer, 2014)

Simulation of Geological Contacts from Interpreted Geological Model Using Multiple-Point Statistics - Alexandre Boucher; Joao Felipe Costa; Luis Gustavo Rasera; Eduardo Motta (Mathematical Geosciences, 2014)

Guava decline: effect of root exudates from Meloidogyne enterolobii-parasitized plants on Fusarium solani in vitro and on growth and development of guava seedlings under controlled conditions - Vicente Martins Gomes; Ricardo Moreira Souza; Silvaldo Felipe da Silveira; Alexandre Macedo Almeida (European Journal of Plant Pathology, 2013)

The influence of litter quality on the relationship between vegetation and below-ground compartments: a Procrustean approach - Francy J. G. Lisboa; Guilherme M. Chaer; Ederson da C. Jesus; Sérgio M. de Faria; Fernando S. Gonçalves; Felipe M. Santos; Alexandre F. Castilho; Ricardo L. L. Berbara (Plant and Soil, 2013)

An antimicrobial diketopiperazine alkaloid and co-metabolites from an endophytic strain of Gliocladium isolated from Strychnos cf. toxifera - Hector Henrique Ferreira Koolen; Elzalina Ribeiro Soares; Felipe Moura Araújo da Silva; Antonia Queiroz Lima de Souza; Lívia Soman de Medeiros; Edson Rodrigues Filho; Richardson Alves de Almeida; Ismael Alexandre Ribeiro; Cláudia do Ó Pessoa; Manoel Odorico de Morais; Patrícia Marçal da Costa; Afonso Duarte Leão de Souza (Natural Product Research, 2012)

Chronic methylphenidate administration alters antioxidant defenses and butyrylcholinesterase activity in blood of juvenile rats - Felipe Schmitz; Emilene Barros da Silva Scherer; Maira Jaqueline da Cunha; Aline Andrea da Cunha; Daniela Delwing Lima; Débora Delwing; Carlos Alexandre Netto; Angela Terezinha de Souza Wyse (Molecular and Cellular Biochemistry, 2012)

Repeatability of full-sib sugarcane families across harvests and the efficiency of early selection - Cássia Ângela Pedrozo; Márcio Henrique Pereira Barbosa; Felipe Lopes da Silva; Marcos Deon Vilela de Resende; Luiz Alexandre Peternelli (Euphytica, 2011)

Improving the quality of African robustas: QTLs for yield- and quality-related traits in Coffea canephora - Thierry Leroy; Fabien De Bellis; Hyacinthe Legnate; Edmund Kananura; Gustavo Gonzales; Luiz Felipe Pereira; Alan Carvalho Andrade; Pierre Charmetant; Christophe Montagnon; Philippe Cubry; Pierre Marraccini; David Pot; et al. (Tree Genetics & Genomes, 2011)

Selection of snap bean recombined inbred lines by using EGT and SSD - Felipe Oliveira Vilela; Antonio Teixeira do Amaral Júnior; Silvério de Paiva Freitas Júnior; Alexandre Pio Viana; Messias Gonzaga Pereira; Marcelo Geraldo de Morais Silva (Euphytica, 2009)

Effects of gamma-decanolactone on seizures induced by PTZ-kindling in mice - Paulo Alexandre de Oliveira; Felipe Luis Lino; Shandale Emanuele Cappelari; Lucimar Filot da Silva Brum; Jaqueline Nascimento Picada; Patrícia Pereira (Experimental Brain Research, 2008)

Comparison of transcription of multiple genes during mycelia transition to yeast cells of Paracoccidioides brasiliensis reveals insights to fungal differentiation and pathogenesis - Juliana Alves Parente; Clayton Luiz Borges; Alexandre Melo Bailão; Maria Sueli S. Felipe; Maristela Pereira; Célia Maria de Almeida Soares (Mycopathologia, 2008)

Platelet-Activating Factor Modulates a Secreted Phosphatase Activity of the Trypanosomatid Parasite Herpetomonas muscarum muscarum - Patricia M.L. Dutra; Felipe A. Dias; Claudia O. Rodrigues; Alexandre Romeiro; Marcia Attias; Wanderley De Souza; Angela H.C.S. Lopes; José Roberto Meyer-Fernandes (Current Microbiology, 2001)